1998
DOI: 10.3138/jcfs.29.2.373
|View full text |Cite
|
Sign up to set email alerts
|

What’s Love Got to Do with It?: Economic Viability and the Likelihood of Marriage Among African American Men

Abstract: A key goal of this research was to determine whether selected economic and demographic factors explaining entry into marriage among African American men are constant across time, or are salient only at certain historical junctures. The study uses 1970-1990 Public Use Microdata Sample 5% Census data files from metropolitan areas with large African American populations. The study’s key innovation is the use of multilevel analysis to link macro-level indicators with individual level characteristics and marital ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Even similar studies that were conducted about the reluctant to marriage and increase the age of it couldn't fill this research gap. Because these researches have investigated the marriage's obstacles (negative attitude) and advantages of it (positive attitude) from the quantitative view and they never investigated in way of qualitative and in-depth the formation of this process (Davis & et al, 1997., James, 1998., White & Cones, 1999., King & Allen, 1999. For example, it is imagined before that the economic factors are one of reluctant to marriage in youth, but the economic factors were allocated 26 codes in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Even similar studies that were conducted about the reluctant to marriage and increase the age of it couldn't fill this research gap. Because these researches have investigated the marriage's obstacles (negative attitude) and advantages of it (positive attitude) from the quantitative view and they never investigated in way of qualitative and in-depth the formation of this process (Davis & et al, 1997., James, 1998., White & Cones, 1999., King & Allen, 1999. For example, it is imagined before that the economic factors are one of reluctant to marriage in youth, but the economic factors were allocated 26 codes in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers reported that couples were thinking differently about marriage and that men not marrying and being in relationships with the mothers of their children was not unique in the Black community (James, 1998;Zavodny, 1999). For the Black community not marrying as a result of a pregnancy has been prevalent since the Great Migration of the 1920s.…”
Section: Marriage In the 21st Centurymentioning
confidence: 99%
“…The proposition of this qualitative study suggests that Black communities were in the process of a cultural shift toward the endorsement of nonmarital births. Several studies (Bowman & Sanders, 1998;Cohen, 2003;James, 1998;Nomaguchi, Brown & Leyman, 2012;Smith & Beaujot, 1999) provide a female voice on nonmarital births and marriage, but very few with the male voice. A book by Edin, Kefalas, & Furstenberg (2011) Promises I can keep: Why poor women put motherhood before marriage explored the topic in detail primarily from the female voice.…”
Section: Marriage In the 21st Centurymentioning
confidence: 99%
“…Changes in marriage have been linked either to changes in male economic opportunity or to female economic independence. In essence, the increasing economic marginality of Black males make them less attractive as potential husbands because they cannot fulfill the provider role in a marriage (James, 1998). Because of this restricted marriage pool and the circumstances in which women find themselves (e.g., being less educated, low-income, and with multiple children), they are also more likely to date a man with a history of criminal activity (Miller & Browning, 2000).…”
Section: Marriage Patternsmentioning
confidence: 99%